Characterisation of a thermionic plasma source apparatus for high-density gaseous plasma antenna applications. (9th November 2020) - Daykin-Iliopoulos, Alexander; Bosi, Franco; Coccaro, Fabio; Magarotto, Mirko; Papadimopoulos, Athanasios; De Carlo, Paola; Dobranszki, Cristian; Golosnoy, Igor; Gabriel, Steve
Abstract: A thermionic plasma source apparatus has been developed and characterised for high-density gaseous plasma antenna (GPA) applications. The system produces a cylindrical plasma column which is 100 mm long with a diameter of 8 mm and operates with a total plasma power consumption of 70 to 200 W, depending mainly on the DC discharge current. The plasma column electron density and temperature is measured via microwave interferometry and optical emission spectroscopy. The plasma properties are investigated for Ar, Kr and Xe at pressures from 1 to 4 mbar. The system has demonstrated higher electron densities (>10 19 m −3 ) at low pressures (<2 mbar) than has been experimentally achieved before for GPA applications. This could allow for high gain GPA operation comparable to that of conventional metallic antennas. Additionally, the source has demonstrated operation over a wide range of electron densities, from 2 × 10 18 to 1 × 10 19 m −3, which can allow for frequency hopping. The plasma columns electron temperature remains around 1.5 eV for argon, largely uninfluenced by the pressure or discharge current. These plasma column measurements obtained are used to analyse the plasma properties influence on GPA performance. This analysis indicates that at high density operation, a gain is achieved which is only 22% lower than that of the conventional metallic antenna. Furthermore, the density ranges demonstrated could enable wide-range frequency hopping of over 100 MHz, with a gain greater than 1.3 dBi.